Sport massage Sebagai Solusi Cepat dalam Mengurangi Kelelahan Otot Setelah Aktivitas Fisik Intensitas Tinggi: Studi Literatur - Abdillah, Muhammad Zakka Fikri; Hartoto, Setiyo; Ningsih, Yuni Fitriyah; Al Ardha, Muchamad Arif; Fathir, Lucy Widya (Jurnal Keolahragaan, 2025)
The purpose of this study was to determine the effectiveness of sports massage as an alternative in reducing muscle fatigue after high-intensity exercise. The method used was a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Secondary data was collected from various indexed journal literature studies on the effect of sports massage in reducing muscle fatigue after high intensity interval training (HIIT). The review of 10 articles showed that sports massage is effective in significantly reducing blood lactic acid after high-intensity exercise. Eight studies showed a p < 0.05, indicating a significant difference in reducing lactic acid levels after sports massage intervention. One study showed no significant difference between sports massage and stretching (p = 0.382), although both were effective individually. One study was not significant (p > 0.05) in reducing lactic acid. The combination of massage and active recovery proved significant. The use of sports massage has been shown to reduce fatigue after high-intensity physical activity. This is due to the significant reduction in lactic acid, overcoming delayed onset muscle soreness and muscle fatigue, and increasing flexibility.